Pengaruh Gaya Hidup terhadap Pengelolaan Keuangan Mahasiswa: Studi Kasus Mahasiswa Fekultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sulthan Thaha Saifudin Jambi Angkatan 2020 - Wanda Lestari; Titin Agustin Nengsih; Kurniyati Kurniyati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to determine the influence of lifestyle on student financial management. The method in this research uses quantitative methods. The sample selection process can use a simple random sampling technique, namely taking samples from each population randomly without paying attention to the strata in the population. The type of data used is primary data. The data analysis technique uses simple linear regression, validity test, reliability test, classical assumption test (normality test), hypothesis test (t test) and coefficient of determination (r-square). The results of the research prove that lifestyle has a positive and significant effect on student financial management.The better a person's lifestyle, the better their financial management will be.